Analysis of WMSDs Among Network Division Employees at PT. XYZ Using the Nordic Body Map and ROSA Methods - Dzaki Syahriar Ahmad; Rizqi Novita Sari (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2025)
Intensive computer use without ergonomic considerations poses risks of Work-Related Musculoskeletal Disorders (WMSDs) for PT. XYZ employees, who often work in uncomfortable positions. This study identified risk factors using the Nordic Body Map and ROSA methods. Results revealed high complaints in the upper neck and right shoulder, with 4 out of 5 employees at high risk due to non-ergonomic work postures and facilities. Recommendations include workplace layout improvements, posture training, and stretching routines to reduce WMSD risks and enhance employee well-being.